PENGARUH CITRA MEREK TERHADAP PEMBELIAN PRODUK FASHION - Heidi Surya Utama; Cintri Anjani Rahmada Putri; Isabella Isabella (PROSIDING SERINA, 2021)
In the current era, there is a lot of competition for fashion products, so many local and international brands make marketing strategies to achieve the desired target. Fashion is a product that is in great demand from various circles. The purpose of this study was to determine the effect of brand image on purchasing decisions of fashion products. This type of research is filling out a questionnaire, with a total of 59 respondents from various circles. The data collection technique in this study uses google form as a questionnaire. Based on the results of research analysis brand image and product quality have a positive influence on purchasing decisions of a fashion product itself, based on available data Price is the main determinant in making purchasing decisions for a fashion product. The conclusion of this study is that a product first sees the price before the brand and the quality to be purchased. Inthecurrentera,thereisalotofcompetitionforfashionproducts,somanylocalandinternationalbrandsmakemarketingstrategiestoachievethedesiredtarget.Fashionisaproductthatisingreatdemandfromvariouscircles.Thepurposeofthisstudywastodeterminetheeffectofbrandimageonpurchasingdecisionsoffashionproducts.Thistypeofresearchisfillingoutaquestionnaire,withatotalof59respondentsfromvariouscircles.Thedatacollectiontechniqueinthisstudyusesgoogleformasaquestionnaire.Basedontheresultsofresearchanalysisbrandimageandproductqualityhaveapositiveinfluenceonpurchasingdecisionsofafashionproductitself,basedonavailabledataPriceis themaindeterminant inmakingpurchasingdecisionsforafashionproduct.The conclusion ofthis study isthat a product first sees theprice before the brand and the quality to be purchased.